PENDAMPINGAN DAN PELATIHAN IT (KOMPUTER) BAGI MUSLIMAT NU KOTA MALANG - Hasanah, Naimatul; Nuril Badria (ABIDUMASY Jurnal Pengabdian Kepada Masyarakat, 2023)
This scientific paper assistance aims to improve IT skills for Muslimat NU in Malang City. The determination of this training was motivated by the results of field observations by the community service team of the Faculty of Economics and Business, Islamic University of Malang on the low IT skills of Muslimat NU in Malang City. Observations showed that Muslimat NU in Malang had difficulties in carrying out administrative activities, even though in the organization there were many things that required expertise in IT, one of which was for correspondence and many others. Based on these problems, this IT training assistance activity was carried out using a qualitative descriptive method, namely: (1) lectures in delivering material about MS. Word and Digital Literacy (2) practice provided in the form of training and assistance in usingtools based on Ms application. word. This IT training mentoring activity was attended by all Muslimat NU women in Malang City. Muslim women are able to operate computers (3) all Muslim women are able to operate Microsoft Word and are able to use it for organizational administrative purposes.